Hypoglychemic activity of Moringa oleifera extract in streptozotocin-induced diabetic rats - Rabiatul Adawiyah; Tri Setyawati; Rahma Badaruddin; Listawati (Acta Biochimica Indonesiana)
Background: Diabetes mellitus, particularly Type 2 (T2DM), is a global health concern characterized by high blood glucose levels and insulin resistance.